Association of High Levels of Bullying and Cyberbullying with Study Time Management and Effort Self-Regulation in Adolescent Boys and Girls - Jose Luis Solas-Martínez; Alba Rusillo-Magdaleno; Ramón Garrote-Jurado; Alberto Ruiz-Ariza (Education Sciences)
This study examined the association between bullying and cyberbullying (both victims and perpetrators) and resource management strategies for learning in students aged 10 to 16. A cross-sectional study was conducted with 1330 Spanish students (48.95% boys; mean age = 13.22 ± 1.75 years). Learning strategies were assessed using the Motivated Strategies for Learning Questionnaire (MSLQ), bullying levels with the European Bullying Intervention Project Questionnaire (EBIP-Q), and cyberbullying with the European Cyberbullying Intervention Project Questionnaire (ECIP-Q). ANCOVA and binary logistic regression were used to analyze associations and exposure risk. Girls who were victims of bullying and cyberbullying showed significantly lower scores in study time management (−5.9%, p = 0.001 for bullying; −6.2%, p = 0.025 for cyberbullying) and effort self-regulation (−7.7%, p < 0.001; −8.3%, p = 0.002). Victimized girls were also up to 4.2 times more likely to struggle with effort self-regulation. Female aggressors exhibited up to 10.2% lower effort self-regulation, while male cyberbullies had 9.6% lower study time management compared to their peers and a 4.4 times greater risk of low effort self-regulation (p < 0.001). These findings emphasize the importance of designing targeted school interventions to strengthen self-regulation strategies, particularly for female victims and male cyberbullies, contributing to improved academic outcomes.